2003
DOI: 10.1103/physrevd.67.065015
|View full text |Cite
|
Sign up to set email alerts
|

Charge neutrality effects on two-flavor color superconductivity

Abstract: Four different phases of the two-flavor quark system, i.e., the normal quark matter and color superconducting phases with and without the charge neutrality condition, are investigated in the framework of the SU͑2͒ Nambu-Jona-Lasinio model. It is found that the color superconducting phase without charge neutrality has the lowest thermodynamic potential, and the charge neutral systems have higher thermodynamic potentials. However, the BCS pairing always lowers the system's thermodynamic potential, i.e., for both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
137
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 24 publications
5
137
0
1
Order By: Relevance
“…Integrating out the quark fields and working in the framework of the Matsubara and Nambu-Gorkov formalism we obtain the following MFA quark thermodynamical potential (a detailed procedure of calculation can be found in Refs. [17][18][19] )…”
Section: The Quark Matter Phasementioning
confidence: 99%
“…Integrating out the quark fields and working in the framework of the Matsubara and Nambu-Gorkov formalism we obtain the following MFA quark thermodynamical potential (a detailed procedure of calculation can be found in Refs. [17][18][19] )…”
Section: The Quark Matter Phasementioning
confidence: 99%
“…As a result, one may deal with a thermodynamic potential Ω which depends on two variables ∆, σ or, equivalently, ∆, m ≡ m 0 + σ , only. Then, the expression for the thermodynamic potential Ω can be calculated with the help of (13) (see also, e.g., [11]):…”
Section: Gap Equations and Color Neutrality Conditionmentioning
confidence: 99%
“…Indeed, since the lump of quark matter, which might be created after heavy ion collisions, originated from color neutral objects and is surrounded by a color neutral medium, it is expected to be globally color neutral. To fulfill this requirement, usually the local color neutrality constraint is imposed by introducing several new chemical potentials, µ 3 , µ 8 , etc, into a NJL model [4,10,11]. Otherwise, there will be produced a chromo-electric field resulting in the flow of color charges, so a homogeneous and color conducting quark medium with nonzero color charge densities is not allowed to be a stable one [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed in the 1960s that the competition between the pair breaking and the pair condensation would induce an unconventional superconducting phase, the Larkin-OvchinnikovFulde-Ferrel (LOFF) state [1]. Recently it was found that if the mismatch is larger than the gap magnitude, a gapless superconducting phase [2,3] or a breached pairing (BP) [4] can be formed in a charge neutral quark matter or in a constrained imbalanced cold atom system, respectively. Another scenario for the ground state at moderate mismatch is the phase separation [5] between of superfluid/superconducting and normal phases.…”
mentioning
confidence: 99%
“…The explicit form of Ω M has been given in Ref. [2] with the Sarma instability [19], 12) in weak coupling, i.e. δµ <<μ.…”
mentioning
confidence: 99%